Does water level affect benthic macro-invertebrates of a marginal lake in a tropical river-reservoir transition zone? - Zerlin, Ricardo Alexandre [UNESP]; Henry, Raoul [UNESP] (Int Inst Ecology, 2014)
Benthic macro-invertebrates are important components of freshwater ecosystems which are involved in ecological processes such as energy transfer between detritus and consumers and organic matter recycling. The aim of this work was to investigate the variation in organism richness, diversity and density of benthic fauna during the annual cycle in Camargo Lake, a lake marginal to Paranapanema River, southeast Brazil. The correlation of environmental factors with community attributes of the macro-benthic fauna was assessed. Since Camargo Lake is connected to the river, we tested the hypothesis that water level variation is the main regulating factor of environmental variables and of the composition and abundance of benthic macro-invertebrates. The results indicated that lake depth varied with rainfall, being the highest at the end of the rising water period and the lowest at the beginning of this period. The sediment granulometry was more heterogeneous at the bottom of the lake by the end of the high water period. The benthic macro-invertebrate fauna was composed by 15 taxa. The Diptera order was represented by seven taxa and had greater richness in relation to other taxa. This group was responsible for 60% of the total abundance of organisms, followed by Ephemeroptera (22%) and Anellida (16%). Significant differences were observed over time in total richness and, in density of Narapa bonettoi, Chaoborus, Ablabesmyia gr. annulata, Chironomus gigas, Larsia fittkau, and Procladius sp. 2. Total taxa richness correlated negatively with water pH, transparency, conductivity, and bottom water oxygen. Higher positive correlations were found between the densities of some taxa and bottom water oxygen, conductivity and very fine sand, silt + clay of sediment, while negative correlations were recorded with organic matter, and fine, medium and coarse sand, bottom water temperature, mean temperature and rainfall. The significant temporal difference in water level was associated with changes in abiotic factors and macro-invertebrate community attributes.

Os macro-invertebrados são componentes importantes de ecossistemas aquáticas continentais, envolvidos em processos ecológicos como transferência de energia entre detritos e consumidores e, reciclagem de matéria orgânica. O objetivo deste trabalho foi investigar a variação na riqueza de organismos, diversidade e densidade da fauna bentônica durante um ciclo anual na Lagoa do Camargo, marginal ao Rio Paranapanema, sudeste do Brasil. Eventuais relações de fatores ambientais com atributos da comunidade macro-bentônica foram verificadas. Visto que a Lagoa do Camargo é conectada com o rio, nós testamos a hipótese de que a variação do nível de água é o principal fator regulador das variáveis ambientais e da composição e abundância dos macro-invertebrados bênticos. Os resultados indicaram que a profundidade da lagoa variou com a precipitação, sendo mais alta no final do período da enchente e mais baixa no inicio deste período. A granulometria do sedimento foi mais heterogênea no fundo da lagoa no final do período de cheia. A fauna de macro-invertebrados bênticos foi composta de 15 taxa. A ordem Diptera foi representada por sete taxa e tem maior riqueza em relação aos outros taxa. Este grupo foi responsável por 60% da abundância total de organismos, seguido por Ephemeroptera (22%) e Anellida (16%). Diferenças temporais significativas foram observadas na riqueza total e, na densidade de Narapa bonettoi, Chaoborus, Ablabesmyia gr. annulata, Chironomus gigas, Larsia fittkau, and Procladius sp. 2. A riqueza total de taxa correlacionou-se negativamente com pH da água, transparência, condutividade e oxigênio na água do fundo. As mais altas correlações positivas foram encontradas entre as densidades de alguns taxa e oxigênio da água de fundo, condutividade e areia muito fina, silte + argila do sedimento, enquanto que correlações negativas foram obtidas com matéria orgânica, e areia fina, média e grossa, temperatura da água de fundo, temperatura média e precipitação. A diferença temporal significativa do nível de água foi associada a mudanças nos fatores abióticos e nos atributos da comunidade de macro-invertebrados
O nível de água afeta os macro-invertebrados bentônicos de uma lagoa marginal na região de transição rio - represa de zona tropical?
Keywords: Marginal lake; Connectivity; Water level; Benthic fauna; Lagoa marginal; Conectividade; Nível de água; Fauna bêntica